PENGARUH PENGGUNAAN GADGET TERHADAP HASIL BELAJAR IPS SISWA SDN 13 MUARADUA - Messy Olvika Sandi; Yasir Arafat; Eni Heldayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of using gadgets on social studies learning outcomes of grade five students of SDN 13 Muardua. The research was carried out in the even semester of 2022/2023. The study used the Experimental method with True Experimental Design techniques in the form of a Pretest-Posttest Control Group Design. The sample in the study was class V-A as a control totaling 29 students, and class V-B as an experimental class totaling 31 students. The research instrument used is a written test in the form of multiple-choice questions as many as 10 questions on the material Location of Geography and Indonesian Astronomy of Natural Appearance (Landscape). Based on the data from the results of the research that has been carried out, it can be proven from the results of the final test (posttest) in the experimental class given treatment using gadgets obtained an average value of 59.03 and the control class obtained an average value of 49.31. In addition, through hypothesis testing with the T-test (Independent Sample T-Test), the results obtained that the calculated value of t-table > is 2.776 > 1.672 which means Ha is accepted and Ho is rejected. So it can be concluded that there is influence of the use of gadgets on the social studies learning outcomes of SD Negeri 13 Muaradua. Keywords: Gadget Use, Social Studies Learning Outcomes